Sources of Stress, Family Functioning, and Needs of Families With a Chronic Critically Ill Child: A Qualitative Study - Grandjean, Chantal; Ullmann, Pascale; Marston, Mark; Maitre, Marie-Christine; Perez, Marie-Hélène; Ramelet, Anne-Sylvie; , The OCToPuS Consortium; Lauria, Anne-Laure; Polito, Angelo; Bochaton, Nathalie; Trachsel, Daniel; Schnidrig, Silvia; et al. (Frontiers in Pediatrics, 2021)
PICU hospitalization is particularly stressful for families. When it is prolonged and the prognostic is uncertain, it can significantly and negatively affect the whole family. To date, little is known on how families with a chronic critically ill (CCI) child are affected. This national study explored the specific PICU-related sources of stress, family functioning and needs of families of CCI patients during a PICU hospitalization. This qualitative study was conducted in the eight pediatric intensive care units in Switzerland. Thirty-one families with a child meeting the CCI criteria participated in semi-structured interviews. Interviews, including mothers only (n=12), fathers only (n=8), or mother and father dyads (n=11), were conducted in German, French, or English by two trained researchers/clinical nurses specialists. Interviews were recorded, transcribed verbatim, and analyzed using deductive and inductive content analyses. Five overarching themes emerged: 1) high emotional intensity, 2) PICU-related sources of stress, 3) evolving family needs, 4) multi-faceted family functioning, and 5) implemented coping strategies. Our study highlighted the importance of caring for families with CCI children. Parents reported high negative emotional responses that affect their family functioning. Families experience was highly dependent on how HCPs were able to meet the parental needs, provide emotional support, reinforce parental empowerment, and allow high quality of care coordination.